The Role of Strategic Leadership in the Implementation of Total Quality Management: A Case Study of the African Health Governance - Marvin Nso, Eyong-Echaw; Katavic, Ivica (Global journal of Business and Integral Security, 2025)
This paper is aimed at exploring the role of strategic leadership in the implementation of TQM initiatives in the African hospitals as a means of optimum global health governance. Its main purpose is to summarize / synthesize orient areas for further studies and identify knowledge gaps in various aspects of health governance in Africa. A systematic review approach was used to examine the role of strategic leadership in the implementation of TQM in the African hospitals. This involved the exploration of 34 articles published between the years 2018 and 2024. The study findings clearly indicated that strategic leadership improves institutional healthcare governance, achieve healthcare quality outcomes, and enhances TQM implementation in the African hospitals. Key words: African hospitals, Global health governance, TQM, Strategic leadership.